Pentingnya Landasan Ontologi, Epistimologi, Aksiologi Dan Psikologi Dalam Pengembangan Teori Dakwah - Muhammad Nurul Fadillah (Universitas Islam Negeri Imam Bonjol Padang, 2022)
Development of da'wah theory is part of an effort to run the wheels of life for Muslims so that they adhere to the guidance and order of the Islamic religion which is based on the Al-Quran and hadith. The background of this research is that not all Muslims preach with high knowledge, but according to the abilities and abilities of every Muslim. Of course for scholars it is very necessary to have an effort or endeavor in preaching, namely by developing the theory of da'wah which is very important to understand and implement in order to achieve da'wah that is rahmatan lilalamin. The purpose of this research is to understand, understand, and have a foundation of ontology, axiology, epistemology and psychology in preaching. Because if you don't pay attention to this basis, you will definitely fail in preaching. The form of this study is the research method used, which is a qualitative type and the approach used is descriptive, with a type of literature review study. Data collection techniques are documents, in the form of references from journals, books, and supporting literature. The result of this research is that the ontology foundation reveals the reality that exists, so that it is always updated with the times. The epistemological basis sees reality in a fundamental and comprehensive radical way, da'wah seeks to achieve a closer relationship. The foundation of axiology examines values, with a belief in truth tested in reality. The foundation of psychology influences the mad'u mindset, as well as its interactions to understand mentality and behavior.